Self-selecting the number of repetitions in potentiation protocols enhances jumping performance - Dello Lacono, A.; Beato, M.; Halperin, I. (SportRxiv Preprints, 2020)
Purpose. To investigate if providing athletes with a choice regarding the number of repetitions to complete in a potentiation protocol would enhance jumping performance compared to protocols in which the number of repetitions is predetermined. Methods. Fifteen male basketball players completed four testing sessions separated by 72 hours. On the first session, individual optimum power loads (OPL) in the barbell jump squat were determined. On the following three sessions, athletes completed three sets of three potentiation protocols using OPL jump squats in a partly-randomized order: i) traditional condition included six repetitions per set; ii) self-selected condition included a choice regarding the number of repetition to complete per set; iii) imposed condition included the same number of repetitions per set as the self-selected condition but imposed on the athletes beforehand. Jumping performance was determined as jump squat (JS) test height and measured using a force platform before, 30s, 4 min, and 8 min after completing the protocols. Results. The self-selected condition led to superior jumping performance compared to the two other conditions across all post measures (p<0.05; range: 0.3-1.3 cm). Compared to the traditional condition, the imposed condition led to superior jumping performance across all post measures (range: 0.2-0.45 cm) although not statistically significant at post 4 min and 8 min. Conclusions. Choice provision concerning how many repetitions to complete in a potentiation protocol is a useful performance enhancing strategy. Improved potentiation-fatigue ratio and motivational factors are sought to explain these effects.